PENGARUH SISTEM PELAPORAN, PARTISIPASI MASYARAKAT DAN PEMAHAMAN PERATURAN PEMERINTAH PADA AKUNTABILITAS PENGELOLAAN DANA DESA - Ni Made Meisi Cahyani; Anak Agung Ketut Agus Suardika (UNHI Press, 2020)
In the management of village funds it is demanded that there be an aspect of good governance in which one of the pillars is accountability. The purpose of the study was to determine the effect of the reporting system, community participation and understanding of government regulations on the village fund management accountability. This research was conducted in the villages in the Abiansemal sub-districtof Badung Regency.Method of determiningthe sample with a purposive sampling method. Data collection is done by distributing questionnaires. While the data analysis technique used id multiple linear regression. Based on the results of this study indicate that the reporting system, community participation and understanding of government regulations have a positive and significant effect on the accountabilityof the village fund management. This shows the better the reporting system, community participation and understanding of government regulations the better accountabilityof the village fund management carried out by village official. Based on the above conclusions, it is suggested that there is a need for choaching or training of the village government for an understanding of village fund management so that in the future a training program can be made or it can also be submitted to the local government.